2020
DOI: 10.1021/acs.jpcc.0c05357
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Stability of Inverted Planar MA-Free Perovskite Solar Cells and Electric Field-Induced Phase Instability

Abstract: Hybrid organic–inorganic perovskite is one of the most promising candidates to replace state-of-art silicon to fabricate low cost solar cells. However, its instability, including intrinsic and operational instability, strongly hinders its real-life applications. Methylammonium (MA)-free, formamidinium (FA)-based perovskite doped by small A-site inorganic cations was developed to tackle the intrinsic instability issue, but the operational instability, especially against the applied electric field, induced by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…It would be caused by the nature of solution-processed polycrystalline perovskite film, where the perovskite surface and bulk grain boundaries are important sources for nonradiative recombination, which can heavily trapping photogenerated charge carriers and thus inhibiting the performance of the device. [37] Researchers have extensively used various techniques such as iodide management, [38,39] additive engineering, [40][41][42] composition engineering, [43,44] grain boundary /surface passivation, [45][46][47] and nonradiative recombination suppression [48,49] in the past few years to improve the quality of MA-free perovskite films. Studies to simultaneously fabricate uniform, high-quality, and large-area perovskite films with modulated crystallization orientation, annihilated defects, and improved device operation stability have rarely been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…It would be caused by the nature of solution-processed polycrystalline perovskite film, where the perovskite surface and bulk grain boundaries are important sources for nonradiative recombination, which can heavily trapping photogenerated charge carriers and thus inhibiting the performance of the device. [37] Researchers have extensively used various techniques such as iodide management, [38,39] additive engineering, [40][41][42] composition engineering, [43,44] grain boundary /surface passivation, [45][46][47] and nonradiative recombination suppression [48,49] in the past few years to improve the quality of MA-free perovskite films. Studies to simultaneously fabricate uniform, high-quality, and large-area perovskite films with modulated crystallization orientation, annihilated defects, and improved device operation stability have rarely been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…However, to make PVK competitive to c-Si, the issues related to device lifetime still need to be addressed. The instability part of PVK film comes mainly from defects (ion migration) 217,218 , pinholes (lattice deformation) 219 , and phase transition 220 , which may accelerate the degradation in presence of water 221 , high temperature 222 , light 223 and electric field 224 . To estimate the potential lifetime of PSCs, the International Electrotechnical Commission (IEC) is normally used based on a series of strict tests, such as UV-light, thermal cycling and damp heating 142 .…”
Section: Sources Of Instabilitymentioning
confidence: 99%
“…Ion migration throughout the bulk perovskite layer can cause a stoichiometric polarization or phase segregation, which may lead to the formation of iodine vacancies and iodine interstitials defects that can cause degradation in the performance of the perovskite. [ 223 ] Zheng et al [ 224 ] fabricated two types of methylammonium‐free perovskites, Rb 0.05 Cs 0.1 FA 0.85 PbI 3 and Cs 0.15 FA 0.85 PbI 3 . Their study in inverted structured devices revealed that the degradation in these type of devices was caused by phase segregation which was triggered by ion migration under electric field and the losses of I − anions and Rb + and Cs + cations captured by the electrodes.…”
Section: Stabilitymentioning
confidence: 99%
“…[ 221 ] To overcome this, several strategies have been studied to reduce the impact of this phenomenon. For example, the research of Zheng and co‐workers [ 224 ] revealed that mixing the precursor solution before its deposition using the spin coating method is one easy way to reduce defect densities and consequently the ion migration in the PSCs. The mentioned mixed 1D/3D perovskites can also be applied to effectively suppress ion migration.…”
Section: Stabilitymentioning
confidence: 99%